Beyond Certification - Poynton, Scott (Taylor & Francis, 2015)
Certification emerged from the 1992 Rio Earth Summit amidst great hope that we would finally begin to address the wicked environmental and social problems facing our globe. Despite a proliferation of certification schemes in twenty-five industry sectors over more than twenty years, the environmental and social ills resulting from destructive and irresponsible exploitation of natural and human resources have grown still worse. Beyond Certification reviews the positive aspects of certification, of which there are many. But more important, it argues that we can no longer afford to gloss over its failures. It is powerfully clear we need a very different approach and set of actions to managing wicked problems like deforestation and exploitation. The book offers one alternative model, based on Values, Transparency, Transformation and Verification, and shares stories of how farsighted people in very large corporations in a number of industries have adopted this model to manage natural resources far more responsibly while also benefitting local communities. Part of the power of this model is that the companies work in partnership with an extensive network of NGOs, local communities, suppliers, and other stakeholders to effect needed change. Beyond Certification does not claim that this VT-TV model is the only solution. Rather, it serves to show how new and seemingly radical thinking can resonate so strongly with many people and companies that it catalyzes positive change. It makes the case for our continuing to invest more thought and proactive energy to develop still other approaches to grappling with the serious issues confronting us all, before it is too late.